Estoques de carbono do solo e fisiologia de feijão-caupi e guandu em sistemas integrados de produção - Igor Costa de Freitas (2022)
Integrated agricultural production systems can increase soil organic carbon stocks over time and contribute to climate change mitigation. However, the choice of species suitable for cultivation in integrated systems is a critical limiting factor for grain and forage production, also interfering in the dynamics of soil organic matter. In this context, the objective was to evaluate variables of growth, nodulation, production and physiology of cowpea and pigeon pea and the stocks and accumulation rates of carbon and total nitrogen in the soil in integrated systems implemented on low productivity pasture in the Cerrado biome. To evaluate the legumes, two experiments were carried out simultaneously, both in a 2 x 4 factorial scheme. The first factor consists in the use of two integrated systems and the second in the evaluation of legumes at four distances (2, 4, 6 and 8 m) from the eucalyptus plantation lines. In the first experiment, the forestry systems (eucalyptus and cowpea) and agrosilvopastoral (eucalyptus, cowpea and buffel grass) were evaluated and, in the second, the silvopastoral systems IPF1 (eucalyptus and pigeon pea) and IPF2 (eucalyptus, pigeon pea and buffel grass). After the legume cultivation, soil samples were collected to determine the soil attributes, being evaluated, in addition to the mentioned treatments, the systems: eucalyptus intercropped with buffel grass; eucalyptus (no cultivation between the lines, but with a history of intercropping); and a low-productivity pasture. A reduction in the number and dry mass of nodules was observed in pigeon pea with distance from the trees. Higher growth, biomass production and photosynthetic activity of cowpea and pigeon pea were observed with distance from eucalyptus planting lines. However, cowpea showed an increase in the weight of 100 grains at distances of 2 and 4 m. In addition, it was observed that buffel grass did not change the productivity of legumes. Additionally, the integration of eucalyptus with legumes or buffel grass increased the labile carbon content in the soil surface layer. The integrated systems also increased the contents and stocks of organic carbon and total nitrogen, non-labile carbon and carbon in the chemical fractions and showed accumulation of 5.22 Mg ha-1 yr-1 and 0.23 Mg ha-1 yr-1 of organic carbon and total nitrogen, respectively, in the layer from 0-40 cm.